Perancangan Aplikasi Mindfulness Pada Platform Ios Untuk Pekerja Jarak Jauh Menggunakan Metodologi Agile Scrum - Yefta Christian; Alvin Matthew Pratama (Universitas Internasional Batam, 2021)
Remote workers tend to experience stress at work because they have to spend more energy communicating and managing work. Stress can cause decreased productivity and can have an impact on health. Mindfulness is a concept that can help manage stress by focusing awareness on the present moment. In this research will develop a mindfulness application to help remote workers control their stress. The practice applied in the application is mindful breathing with box breathing technique. The application will be developed on iOS platform using agile scrum methodology. The result of the study is mindfulness application released on the App Store.